When Social Media Takes Over: Overload, Vulnerability, and Coping Among Young Adults in Marketing-Saturated Social Media - Käppi, Ella (My University, 2026)
Social media has become an important part of young adults' everyday lives. At the same time, however, it has become increasingly marketing-saturated and algorithmically controlled, which is reflected in various negative consequences, such as overload. Although previous research has focused extensively on social media overload, there has been considerably less research on how this overload affects young people's everyday experiences and how they themselves cope with these situations. This study fills this gap by examining how young consumers experience social media overload in a marketing-saturated environment. Furthermore, it explores how overload manifests itself as situational digital vulnerability and what strategies young people develop to cope with these vulnerable experiences. The aim of the study is to better understand young people's experiences of social media overload, situational digital vulnerability, and how they themselves can influence their own digital well-being. The study is based on qualitative in-depth interviews and follows an interpretative and inductive research approach. The results show that social media overload is more than just too much information and noise. It is a holistic feeling that arises from how algorithms select the content to be displayed, how commercialization is constant, and how users are constantly required to pay attention. These factors give rise to situations in which young consumers' perceived agency and control are weakened, and exposure to content and marketing can be experienced as happening outside their control. Digital vulnerability is therefore not a permanent characteristic, but a context-dependent and situational experience that is constructed through the everyday use of social media. The findings of the research show that young consumers do not remain passive when faced with overload and vulnerability. Instead, they seek ways to manage the situation. They may withdraw from situations, curate content, set temporal and spatial boundaries, or even resist algorithms. While these methods may offer temporary relief, they do not necessarily lead to long-term solutions. Young consumers are constantly forced to negotiate asymmetrical power relations in which digital platforms maintain a structural advantage. As a result, self-regulation can feel fragile, require a lot of effort, and be contradictory. By combining literature on social media overload, algorithmic power, marketing saturation, and consumer vulnerability, this study deepens our understanding of young consumers' experiences in today's digital environments. The findings contest individual responsibility and highlight the need to view social media as a structural and commercial environment that shapes users' agency, freedom of choice, and experiences of vulnerability.
Keywords: situational digital vulnerability; social media overload; young adults; marketing-saturated social media; coping; digital self-regulation